Expression Analysis and Functional Validation of DcTPSb1 in Terpene Synthesis of Dendrobium chrysotoxum - Yuxuan Jin; Shuting Zhou; Zhihui Du; Weize Wang; Zhilin Chen (Current Issues in Molecular Biology)
Terpenes are critical components of the floral fragrance component in Dendrobium chrysotoxum, synthesized by terpene synthase (TPS). Analysis of the D. chrysotoxum genome and transcriptional data revealed that the gene DcTPSb1 was significantly up-regulated during flowering periods, showing a strong correlation with the accumulation of aromatic monoterpenes in the floral components of Dendrobium chrysotoxum. Consequently, the DcTPSb1 gene was selected for further analysis. DcTPSb1 exhibited elevated expression levels in flowers among four organs (roots, stems, leaves, flowers) of D. chrysotoxum, with the highest expression observed during the blooming phase, which aligned with the accumulation of volatile terpenes during flowering. DcTPSb1, located in the chloroplasts, was identified as a member of the TPS-b subfamily associated with monoterpenes synthesis, showing close phylogenetic relationships with homologous proteins in related plant species. An analysis of the promoter region of DcTPSb1 indicated that it may be regulated by methyl jasmonate (MeJA) responsiveness. Functionally, DcTPSb1 was shown to catalyze the conversion of geranyl diphosphate (GPP) to linalool, ocimene, and (-)-α-pinitol in vitro. Overexpression of DcTPSb1 in tobacco resulted in a significant increase in terpenoid release during the blooming stage; however, the up-regulated substances did not include their catalytic products. The classification of DcTPSb1 as a terpene synthase capable of producing multiple products provides valuable insights into the complex biosynthesis of terpenes in orchids. These findings enhance our understanding of the functional diversity of DcTPSb1 and the processes involved in terpene biosynthesis in orchids.